1985
DOI: 10.1080/00288233.1985.10420937
|View full text |Cite
|
Sign up to set email alerts
|

Adjustment factors for lamb weaning weight

Abstract: Nine methods of adjusting lamb weaning weight for the effects of age-of-dam, sex, birth-rearing rank, and weaning age were compared. Evaluated several ways, the effectiveness of the methods did not differ very much. It is concluded that the best adjustment procedures are the combined additive and multiplicative, or multiplicative alone. An exception is adjustment for weaning age effects, which should be additive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2015
2015
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
1
0
1
Order By: Relevance
“…By contrast, CV for the various effect classes indicated that multiplicative adjustment factors tended to equalize variances among classes and, therefore, more nearly equalized impacts on EBV of weaning weight records from different types of lambs, but would overcompensate for the larger SD observed in single lambs. Thus, our results agree with previous studies that indicated that accounting completely for both heterogeneity of variance among effect classes and flock differences in adjustment factors would require relatively complex adjustment protocols [9, 15]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…By contrast, CV for the various effect classes indicated that multiplicative adjustment factors tended to equalize variances among classes and, therefore, more nearly equalized impacts on EBV of weaning weight records from different types of lambs, but would overcompensate for the larger SD observed in single lambs. Thus, our results agree with previous studies that indicated that accounting completely for both heterogeneity of variance among effect classes and flock differences in adjustment factors would require relatively complex adjustment protocols [9, 15]. …”
Section: Discussionsupporting
confidence: 92%
“…These relationships allowed the prediction of flock-specific adjustment factors to be extended to larger numbers of flocks, because derivation of flock-specific factors required only an estimate of the mean weights of lambs in the reference class for each flock. These results conflict, in part, with those observed in 12 large New Zealand Romney flocks [15, 16]. In those flocks, significant variation was observed among flocks and years in adjustment factors for effects of lamb sex, birth-rearing type and dam age, but no association was reported between resulting factors and flock means for weaning weights.…”
Section: Discussioncontrasting
confidence: 59%